Investigating The Effect Of Leader-Member Exchange And Psychosocial Safety Climate On Employee Performance The Mediating Role Of Work Engagement - Amalia, Lia; Wafiq Suharyanto, Wahyu; meria, lista; Roespinoedji, Djoko (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the study is to investigate the effect of leader-member exchange (LMX) and psychosocial safety climate (PSC) on employee performance. Integrating the literature on leader-member exchange and psychosocial safety climate theories, the researcher also investigated the role of work engagement in mediating the effect of leader-member exchange (LMX) and psychosocial safety climate (PSC) on employee performance. The study was conducted to 272field employees working for three mineral exploration drilling service companies in Indonesia. Structural equation modeling was used to test the hypothesized effect of the investigated variables. The results of hypotheses testing provide evidence that high quality leader-member exchange (LMX) and psychosocial safety climate (PSC) are well proven to enhance work engagement and employee performance in mineral exploration drilling industry in Indonesia. The study also emphasizes the value of high leader-member exchange and psychosocial safety climate for enhancing work engagement. These high leader-member exchange, psychosocial safety climate and work engagement, in turn also enhance employee performance.